The effect of workplace environment on employee’s performance in Petronas Carigali Sdn Bhd, Bintulu / Nursuliza Syairah Rosdi - Rosdi, Nursuliza Syairah (Faculty of Business and Management, 2017)
The work environment which consists of several factors gives an impact on the way the employees perform their work. A comfortable and all-inclusive workplace environment will enhance the employee’s performance and boost their organizational performance. The objective of the study was to investigate the effect of workplace environment on employee’s performance in Petronas Carigali Sdn Bhd, Bintulu. The target population was all the employees at Petronas Carigali Sdn Bhd which the total number was 838 employees. The sample size included a total of 265 employees. Descriptive research design was adopted for the study. The study used primary data which was collected by questionnaire where the data then, analysed using descriptive statistics that included frequencies, mean scores, standard deviations, and percentages. From the findings, the study concluded that work environmental factors that influenced employee’s performance were physical environment factors, rewards, management style, training and development, and work-life balance. The findings revealed that employees satisfied with these factors. The study recommends that Petronas Carigali Sdn Bhd need to ensure that the workplace environment is comfortable enough that can support employees’ performance which can be done by improving the working conditions. The researcher also recommends further studies to be carried out on other oil and gas company for a broader perspective on the relationship between work environment and employees’ performance.